The Enigmatic Kikuchi-Fujimoto Disease: A Case Report and Review - Hassan Tariq; Vinaya Gaduputi; Arsalan Rafiq; Roopalekha Shenoy (Case Reports in Hematology)
We report this case of a 33-year-old African American woman who presented to the clinic with preauricular and submandibular masses that she had noticed 6 weeks earlier. She gave a remote history of noticing bilateral cervical masses 3 years prior to this presentation that had not been investigated at the time and resolved spontaneously. Excisional biopsies of the cervical lymph nodes showed morphologic and immunophenotypic findings suggestive of Kikuchi Fujimoto disease (KFD). KFD is an uncommon, self-limited, and perhaps an underdiagnosed entity with an excellent prognosis. It mimics malignant lymphoma in presentation and therefore an accurate clinicopathological differentiation is crucial.